EVALUASI KINERJA SIMPANG BERSINYAL (Studi Kasus: Jalan KH. Wahid Hasyim Jombang) - Amudi, Abdiyah (Reaktom : Rekayasa Keteknikan dan Optimasi, 2016)
Population of massive people caused the trafic crowded, and demand to good transportation as personal such as two wheels aslo four wheels getting high. That condition needs attention especially on the intersection. Unbalance of vehicle numbers with road numbers which is already provided of green wendesday cause delay and queue long enough on the intersection. Phase management plan and optimum cycle timing are expected to increase its capacity on the intersection. By getting that situation so the writer conduct study about phase and optimum cycle timing on the intersection at KH. Wahid Hasyim Jombang street by using counting method MKJI 1997 and got side obstacle arround A arm with intermediate obstacle, on B arm got high obstacle, on C and D arm got low obstacle. So that it needs solution by fixing side obstacle arround the branch, widening the branch and management of private vehicle and also special heavy transport to closer B (KH. Wahid Hasyim street) in rush hours of morning and eveningKeyword : Signalize Branch, MKJI 1997, Jombang